Epistolografia i Emigracja. Perspektywy badawcze. Turyn, 6–7 października 2022 r. - Guzman, Daniel (Archiwa – Kancelarie – Zbiory, 2022)
Sprawozdanie z konferencji "Epistolografia i Emigracja. Perspektywy badawcze". Turyn, 6–7 października 2022 r.